The potential establishment of cash waqf in Senegal : a study based on Malaysian experience - Dieng, Mouhamadou Moctar (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2019)
This research explores the potential establishment of cash waqf in Senegal a case study of the Malaysian experience. The research considers how cash waqf in Senegal, can be used successfully and competently for positive impacted on the needy and how such important institution can be sustained over long time. The problem statement of the research in the needs to opposite the tendency of extreme poverty among the Senegalese population within which Muslims constitute the majority. This result in exploring the use of cash waqf as effective instrument for reducing poverty among the Muslim community in Senegal. The methodology employed for this research are qualitative, descriptive and quantitative library based. This study obtained the input of scholars from different major schools. Which support the feasibility cash waqf and the feasibility of introducing it in Senegal.